17-Β-Estradiol and Phytoestrogens Elicit No Production and Vasodilatation Through pi3k Pka and Egf Receptors Pathways, Evidencing Functional Selectivity - Garcia Huidobro-Toro, J; Acuna-Castillo, C; Valdes-Henriquez, D; Donoso-Gomien, M (Elsevier B.V., 2024)
Endothelial cells express multiple receptors mediating estrogen responses; including the G protein-coupled estrogen receptor (GPER). Past studies on nitric oxide (NO) production elicited by estrogens raised the question whether 17-β-estradiol (E2) and natural phytoestrogens activate equivalent mechanisms. We hypothesized that E2 and phytoestrogens elicit NO production via coupling to distinct intracellular pathways signalling. To this aim, perfusion of E2 and phytoestrogens to the precontracted rat mesentery bed examined vasorelaxation, while fluorescence microscopy on primary endothelial cells cultures quantified single cell NO production determined following 4-amino-5-methylamino-2′,7′-difluoroescein diacetate (DAF) incubation. Daidzein (DAI) and genistein (GEN) induced rapid vasodilatation associated to NO production. Multiple estrogen receptor activity was inferred based on the reduction of DAF-NO signals; G-36 (GPER antagonist) reduced 75 % of all estrogen responses, while fulvestrant (selective nuclear receptor antagonist) reduced significantly more the phytoestrogens responses than E2. The joint application of both antagonists abolished the E2 response but not the phytoestrogen-induced DAF-NO signals. Wortmannin or LY-294002 (PI3K inhibitors), reduced by 90% the E2-evoked signal while altering significantly less the DAI-induced response. In contrast, H-89 (PKA inhibitor), elicited a 23% reduction of the E2-induced signal while blocking 80% of the DAI-induced response. Desmethylxestospongin-B (IP3 receptor antagonist), decreased to equal extent the E2 or the DAI-induced signal. Epidermal growth factor (EGF) induced NO production, cell treatment with AG-1478, an EGF receptor kinase inhibitor reduced 90% DAI-induced response while only 53% the E2-induced signals; highlighting GPER induced EGF receptor trans-modulation. Receptor functional selectivity may explain distinct signalling pathways mediated by E2 and phytoestrogens. © 2024